2010
DOI: 10.1007/s10620-010-1368-1
|View full text |Cite
|
Sign up to set email alerts
|

Fellow Involvement During Colonoscopy Does Not Reduce Adenoma Detection Rate

Abstract: Colonoscopy is effective in reducing the morbidity and mortality of colorectal cancer (CRC). However, colonoscopy is a technical procedure that requires expertise to maximize accuracy, and an adequate procedure volume is necessary to achieve competence [1]. Few studies have examined if gastroenterology (GI) fellows, who have less endoscopy experience than their attending physicians, are less likely to identify adenomas and cancers.We performed a retrospective review of 1,190 patients who underwent age-appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The adenoma detection rate (ADR), calculated as the proportion of colonoscopies with an adenoma, for an endoscopist has been found to be directly associated with prevention of subsequent colorectal cancer 2 . It is influenced by patient age and gender, bowel prep quality, caecal intubation rates, withdrawal time, endoscopic technique, time of day and varies by endoscopist 3–17 . Both the American Society for Gastrointestinal Endoscopy and the American College of Gastroenterology have recommended an adenoma detection rate of 15% in women and 25% in men as a measure of quality colonoscopy 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The adenoma detection rate (ADR), calculated as the proportion of colonoscopies with an adenoma, for an endoscopist has been found to be directly associated with prevention of subsequent colorectal cancer 2 . It is influenced by patient age and gender, bowel prep quality, caecal intubation rates, withdrawal time, endoscopic technique, time of day and varies by endoscopist 3–17 . Both the American Society for Gastrointestinal Endoscopy and the American College of Gastroenterology have recommended an adenoma detection rate of 15% in women and 25% in men as a measure of quality colonoscopy 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The study by Nishizawa, Gkolfakis, and Friedman was letters and excluded as we could not perform the quality assessment. [35][36][37] previous meta-analysis. 38 Also, we considered the article by Kim 39 ineligible for inclusion, since the comparison in Kim's study did not elaborate whether the fellow performed colonoscopy alone or under supervision of attending physician/experts.…”
Section: Discussionmentioning
confidence: 99%
“…Kim's article 34 was excluded because it was not a study inspecting the effect of fellow involvement on colonoscopy outcomes, but rather a study of a new colonoscopy method. The study by Nishizawa, Gkolfakis, and Friedman was letters and excluded as we could not perform the quality assessment 35–37 . For de Jonge et al., we could not extract the required data and were not able to verify the data as reported in the previous meta‐analysis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, publication bias could have led to selection of studies with higher ADRs and positive outcomes. Previous studies, which showed no effect or a negative effect on ADRs with fellow involvement during colonoscopy, were only published as letters to the editor or brief correspondence [12,13].…”
Section: Discussionmentioning
confidence: 99%